Are some life-history strategies more vulnerable to the genetic consequences of habitat fragmentation? A case study using South Australian Caladenia R. Br. (Orchidaceae) species - Farrington, Lachlan (Universidad de Costa Rica, 2015)
Habitat fragmentation, through land clearing, has been attributed in the demise of many species of plants and animals throughout the world (Kinzig and Harte 2000). Not surprisingly, much research effort has been devoted toward understanding the dynamics of populations subject to fragmentation.